Capacity mechanisms on Central European electricity markets: Effects on consumers, producers and technologies until 2033 - Thure Traber (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The reduced attractiveness of investments in reliable power plants under conditions of liberalized markets and the transition towards renewable energies has brought a discussion on capacity policies to Europe. We use a partial equilibrium model to compare important effects of three basic policies. A strategic reserve policy and a capacity market policy with administratively set capacity targets, and the obligation of generators to hold certificates of reliable capacities in relation to their supply. We find important differences of policies for consumers and producers that are depending on existing power plant structure and the elasticity of demand particularly in the medium term perspective until the year 2023. In the longer term until 2033 the results differ less pronounced. However, for the German case we demonstrate the potential to effectively reduce the burden on the economy to achieve a prescribed target through the implementation of a capacity certificate system.
Keywords: C63; D47; D61; 330; electricity market; capacity mechanism; investment model